2007
DOI: 10.1128/mcb.02384-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Component of the Human Minichromosome Maintenance Complex

Abstract: Minichromosome maintenance (MCM) complex replicative helicase complexes play essential roles in DNA replication in all eukaryotes. Using a tandem affinity purification-tagging approach in human cells, we discovered a form of the MCM complex that contains a previously unstudied protein, MCM binding protein (MCM-BP). MCM-BP is conserved in multicellular eukaryotes and shares limited homology with MCM proteins. MCM-BP formed a complex with MCM3 to MCM7, which excluded MCM2; and, conversely, hexameric complexes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(120 citation statements)
references
References 41 publications
10
109
1
Order By: Relevance
“…Following the first identification in humans, several studies aimed to characterize and elucidate the functions of MCM-BP. Co-immunoprecipitation analysis showed that human MCM-BP interacts with all MCM subunits, except Mcm2; conversely, Mcm2 fails to recover MCM-BP (26). A similar pattern of interaction between MCM-BP and MCM subunits was observed in Xenopus laevis (27), suggesting that an alternative MCM complex is formed when Mcm2 is replaced by MCM-BP.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Following the first identification in humans, several studies aimed to characterize and elucidate the functions of MCM-BP. Co-immunoprecipitation analysis showed that human MCM-BP interacts with all MCM subunits, except Mcm2; conversely, Mcm2 fails to recover MCM-BP (26). A similar pattern of interaction between MCM-BP and MCM subunits was observed in Xenopus laevis (27), suggesting that an alternative MCM complex is formed when Mcm2 is replaced by MCM-BP.…”
mentioning
confidence: 60%
“…Immunoprecipitation and/or mass spectrometry studies in humans, Xenopus, and fission yeast showed that MCM-BPs (hMCM-BP for human, xMCM-BP for Xenopus, and Mcb1 for fission yeast) interact with all MCM complex subunits, except Mcm2 (26,27,29,30). Therefore, MCM-BP was thought to replace Mcm2 within the MCM complex (26); however, in A. thaliana, AtMcm2 was found to co-purify with ETG1, the A. thaliana MCM-BP ortholog, by mass spectrometry analysis (28).…”
Section: Mcb1 Is Constitutively Expressed and Continuously Interacts mentioning
confidence: 99%
See 1 more Smart Citation
“…The application of TAP method has made considerable progress in mammalian systems (Bürckstümmer et al, 2006;Davison et al, 2009;Drakas et al, 2005;Gottlieb and Jackson, 1993;Holowaty et al, 2003;Jeronimo et al, 2007;Kamil and Coen, 2007;Knuesel et al, 2003;Lehmann et al, 2009;Milewska et al, 2009;Sakwe et al, 2007). For instance, human active SMAD3 protein complex was purified from cell lysates through TAP method, and HSP70 was identified as a novel combination partner of SMAD3 (Knuesel et al, 2003).…”
Section: Tap In Mammalian Systemsmentioning
confidence: 99%
“…Therefore, an additional purification step might be reqired to resolve this trouble, which would be time consuming and lead to more sample loss. Sakwe et al identified a new form of the minichromosome maintenance (MCM) complex in human cells (Sakwe et al, 2007). In another study using the TAP process, Holowaty et al (Holowaty et al, 2003) expressed Epstein-Barr nuclear antigen-1 (EBNA1) protein in fusion with a TAP tag at the C-terminus in human 293T cells.…”
Section: Tap In Mammalian Systemsmentioning
confidence: 99%